“Efecto de tres dosis de desechos industriales en el desarrollo vegetativo de plantones de palma aceitera (Elaeis guineensis jacq) en condiciones de vivero. En el CC.PP.MM de pampa Hermosa- Loreto” - Laureano Sinti, Alex Ivan (2014)
The present investigation entitled "Effect of three doses of industrial wastes in the vegetativa development of seedlings of oíl palm (Elaeis guineensis Jacq) under nursery conditions in CC.PP.MM. Pampa Hermosa - Loreto ", was carried out in order to assess and determine the effect of the highest dose of industrial wastes in the vegetativa development of seedlings of oíl palm nursery conditions, and to establish the relationship between variabílity climatic and vegetativa growth of oíl palm seedlings. Comprehensiva Statistical Design random (RCBD) with four treatments and four replications was used blocks. The variables evaluated were: number of leaves I plant, plant height, stem diameter/plant, root mass, root volume and relationships of vegetativa versus climate variables (average temperatura, relativa humidity and precipitation versus height, diameter and number of leaves/plant). The results indicate that treatment T2 (TO + 80% 20% industrial waste, equivalent to 4 kg of sludge per bag of 20 kg) was the best treatment, the effects are made feasible in obtaining significant results in most of the variables studied, also the climatic conditions of CC.PP.MM. Pampa Hermosa were favorable for the development of oíl palm seedlings in nursery conditions. Keywords: effect, dosage, scrap, industrial, development, vegetativa, nursery, seedlings, variables.